2009
DOI: 10.1177/105268460901900604
|View full text |Cite
|
Sign up to set email alerts
|

The Ecology of Democratic Learning Communities: Faculty Trust and Continuous Learning in Public Middle Schools

Abstract: This cross-sectional explanatory study integrated three complex social processes-democratic community, faculty trust, and organizational learning-into a single testable model. The review of literature demonstrated substantial evidence for the proposed model. The data sources for the study included approximately 3,000 teachers from 79 public middle schools in Pennsylvania and New Jersey. Teachers from each school completed one of three surveys measuring democratic community, faculty trust, or continuous and tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 61 publications
1
20
0
1
Order By: Relevance
“…The origins of trust research drew from the work of Rotter (1967) and others who identified the importance of interpersonal trust and the extent to which learners believe in the trustworthiness of their sources of information—that is, teachers and materials. Those early conceptualizations have broadened considerably in the past 30 years through several significant lines of research that have examined trust and related constructs at the individual and collective levels, in relation to different referents (students, parents, teachers, principals, schools) and in relation to student achievement (e.g., Bryk & Schneider, 2002; Hoy, Gage, & Tarter, 2006; Hoy & Tarter, 2004; Hoy, Tarter, & Hoy, 2006; Hoy, Tarter, & Witkoskie, 1992; Kensler, Caskie, & White, 2009; Seashore Louis, 2007; Sutherland & Yoshida, 2015; Tschannen-Moran, 2001, 2003, 2009). This research has offered a great deal of insight into the social and cultural dynamics of school ecologies, and concepts such as teacher trust in client (Forsyth, 2008) and academic optimism (Hoy et al, 2006) have demonstrated greater potential at predicting student achievement than SES.…”
Section: Educational Leadership and Learning: What Do We Know And Notmentioning
confidence: 99%
“…The origins of trust research drew from the work of Rotter (1967) and others who identified the importance of interpersonal trust and the extent to which learners believe in the trustworthiness of their sources of information—that is, teachers and materials. Those early conceptualizations have broadened considerably in the past 30 years through several significant lines of research that have examined trust and related constructs at the individual and collective levels, in relation to different referents (students, parents, teachers, principals, schools) and in relation to student achievement (e.g., Bryk & Schneider, 2002; Hoy, Gage, & Tarter, 2006; Hoy & Tarter, 2004; Hoy, Tarter, & Hoy, 2006; Hoy, Tarter, & Witkoskie, 1992; Kensler, Caskie, & White, 2009; Seashore Louis, 2007; Sutherland & Yoshida, 2015; Tschannen-Moran, 2001, 2003, 2009). This research has offered a great deal of insight into the social and cultural dynamics of school ecologies, and concepts such as teacher trust in client (Forsyth, 2008) and academic optimism (Hoy et al, 2006) have demonstrated greater potential at predicting student achievement than SES.…”
Section: Educational Leadership and Learning: What Do We Know And Notmentioning
confidence: 99%
“…Although the proposed framework may apply to organizations beyond K-12 schools, the present discussion remains focused on K-12 schools. Foundational to the framework are the following two assertions: (1) Ecological principles govern healthy and sustainable life systems, the systems in which our social systems exist and upon which they depend (Capra, 1996(Capra, , 2002Wheatley & Kellner-Rogers, 1996), and (2) democratic principles govern socially just (Furman & Starratt, 2002) and continuously learning social systems (Kensler, Caskie, Barber, & White, 2009;Slater & Bennis, 1990). The practice of democracy in organizations (Cloke & Goldsmith, 2002;Fenton, 2002;Stohl & Cheney, 2001) and schools (L. Allen & Glickman, 1998;Dewey, 1916;Kensler & Brooks, in press;Koopman, Miel, & Minsner, 1943;Woods, 2005) has a long history and retains an active presence in current educational leadership literature (Cate, Vaughn, & O'Hair, 2006;L.…”
Section: Ecological Democracy: a New Theoretical Framework For Organimentioning
confidence: 99%
“…The practice of democracy in organizations (Cloke & Goldsmith, 2002;Fenton, 2002;Stohl & Cheney, 2001) and schools (L. Allen & Glickman, 1998;Dewey, 1916;Kensler & Brooks, in press;Koopman, Miel, & Minsner, 1943;Woods, 2005) has a long history and retains an active presence in current educational leadership literature (Cate, Vaughn, & O'Hair, 2006;L. Davies, 1999;Furman & Starratt, 2002;Harber & Davies, 1998;Kensler, 2010;Kensler et al, 2009;Murphy, 2002;Woods & Gronn, 2009). Although Furman and Gruenewald (2004) proposed addressing ecological concerns through expanding our conception of social justice, none of the other educational works just cited included ecological principles or concerns as integral to the work of democracy in schools.…”
Section: Ecological Democracy: a New Theoretical Framework For Organimentioning
confidence: 99%
“…), and opportunities for debate and collaborative enquiry (involving dialogue, transparency, free information flows, etc.) (see, e.g., Chaltain, 2010;Cloke & Goldsmith, 2002;Kensler, Caskie, Barber, & White, 2009;Manville & Ober, 2003;O'Hair, Williams, Wilson, & Applegate, 2009;Shields, 2010). The value of the concept of holistic democracy is threefold: It adds to and goes further than studies such as these in explicitly recognizing the intimate relationship between participative decision making and the development of holistic capabilities that include spiritual awareness and involve inner transformation; it explicitly identifies through the four dimensions the distinctive, complementary, and essential components of a rich conception of democracy; and it provides a conceptual framework for considering the overlap and interplay between them.…”
Section: Holistic Democracymentioning
confidence: 99%